2012
DOI: 10.21098/bemp.v14i4.365
|View full text |Cite
|
Sign up to set email alerts
|

Dampak Kebijakan Fiskal Terhadap Output Dan Inflasi

Abstract: Penelitian ini melihat dampak kebijakan fiskal terhadap output dan inflasi serta melihat apakah terdapat diskresi kebijakan fiskal dan bagaimana dampaknya terhadap volatilitas output dan inflasi. Model Vector Error Correction Model (VECM)diaplikasikan atas data triwulanan, mencakup periode 1990 - 2009. Hasil empiris menunjukkan bahwa terdapat hubungan kointegrasi antara pengeluaran pemerintah dan pajak terhadap output dalam jangka panjang. Dalam jangka panjang pengenaan pajak berdampak positif terhadap pertumb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 6 publications
2
9
0
4
Order By: Relevance
“…This is what has happened in Indonesia, where government spending actually hurts inflation volatility in the country. This is in line with the research results by Surjaningsih et al (2012), who found that an increase in government spending causes a decrease in inflation. Furthermore, Azhar et al (2019) stated that government spending has a significant negative effect in the long term, and the negative price is not significant in the short term.…”
Section: Estimation Test Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This is what has happened in Indonesia, where government spending actually hurts inflation volatility in the country. This is in line with the research results by Surjaningsih et al (2012), who found that an increase in government spending causes a decrease in inflation. Furthermore, Azhar et al (2019) stated that government spending has a significant negative effect in the long term, and the negative price is not significant in the short term.…”
Section: Estimation Test Resultssupporting
confidence: 93%
“…There are many studies on inflation from the monetary aspect, but it is still limited from the fiscal aspect. Surjaningsih et al (2012) found that an increase in government spending causes a decrease in inflation, while an increase in taxes causes an increase in inflation. This research's novelty lies in the completeness of the variables used in assessing the volatility of inflation in Indonesia.…”
Section: Literatur Reviewmentioning
confidence: 99%
“…Namun tak hanya kebijakan moneter, kebijakan fiskal pun mampu mengendalikan inflasi. Beberapa penelitian sudah banyak dilakukan untuk melihat dampak kebijakan fiskal bagi pengendalian inflasi, seperti yang dilakukan oleh Surjaningsih, Utari, & Trisnanto (2012), López-Martín, Aguilar, & Samano (2018, Otto & Ukpere (2015), dan lainnya.…”
Section: Gambarunclassified
“…Idealnya, kebijakan fiskal memiliki sifat sebagai automatic stabilizer perekonomian.Artinya,dalamkondisiperekonomian sedang mengalami ekspansi, maka pengeluaran pemerintah seharusnya berkurang atau penerimaan pajak yang bertambah. Sebaliknya jika perekonomian sedang mengalami kontraksi, ke-bijakan fiskal seharusnya ekspansif melalui peningkatan belanja atau penurunan penerimaan pajak, dengan demikian automatic stabilizer kebijakan fiskal masyarakatadanyafungsicountercyclical dari kebijakan fiskal (Surjaningsih dkk, 2012). Salah satu tujuan dari kebijakan fiskal adalah untuk menanggulangi inflasi yang terjadidinegaraberkembang.Padagambar1menyajikanperkembanganinflasidi Indonesia.…”
Section: Pendahuluanunclassified